2015
DOI: 10.1002/jcb.25140
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Apocynin on Cyclosporine A‐Induced Hypertension and Nephrotoxicity in Rats

Abstract: Cyclosporine A (CsA) is the prototype of immunosuppressant drugs that has provided new perspectives in human and veterinary medicine to prevent organ transplant rejection and to treat certain autoimmune diseases and dermatologic diseases. Unfortunately, the treatment with CSA is often limited by severe adverse effects such as hypertension and nephrotoxicity. Some data suggest that reactive oxygen species (ROS) and the oxidative stress play an important role in its pathogenesis, in particular the superoxide (O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…In fact, it has been demonstrated in various experimental models of hypertension, that the increase of blood pressure is linked to ROS increase and it is prevented by the treatment with antioxidants [Gill and Wilcox, ; Palabiyik et al, ]. In an our previous article we have shown that the use of antioxidant apocynin in CsA hypertensive rats restored blood pressure and levels of ROS [Ciarcia et al, ]. Here we have shown that treatment with the new recombinant rMnSOD prevents hypertension induced by OTA and, in addiction, restores lipid peroxidation levels.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In fact, it has been demonstrated in various experimental models of hypertension, that the increase of blood pressure is linked to ROS increase and it is prevented by the treatment with antioxidants [Gill and Wilcox, ; Palabiyik et al, ]. In an our previous article we have shown that the use of antioxidant apocynin in CsA hypertensive rats restored blood pressure and levels of ROS [Ciarcia et al, ]. Here we have shown that treatment with the new recombinant rMnSOD prevents hypertension induced by OTA and, in addiction, restores lipid peroxidation levels.…”
Section: Discussionsupporting
confidence: 54%
“…The mechanism of chronic nephrotoxic diseases has been previously investigated by our research group. In particular, we have demonstrated, in a rat animal model of hypertension induced by cyclosporine, that the increase in ROS production, in particular the O 2 − , was linked to a strong reduction of glomerular filtration rate (GFR) [Ciarcia et al, ]. Since the reduction of antioxidants expression has been shown to be related to an increase of oxidative damage [Klaunig et al, ; Marin‐Kuan et al, ] which contribute to OTA toxicity.…”
mentioning
confidence: 99%
“…NADPH oxidase inhibitor apocynin significantly inhibited the OTA-induced mesangial cytotoxicity and apoptosis. Several studies have demonstrated that apocynin has therapeutic effect on multiple animal disease model including chemically-induced colitis in mice [28], testicular ischemia-reperfusion injury in rats [29], bleomycin-induced lung fibrosis in rats [30], Cyclosporine A-Induced hypertension and nephrotoxicity in rats [31], established alcoholic steatohepatitis rat model [32], and contrast-induced nephropathy in the diabetic rats [33]. Therefore, these findings indicate that the concentrations of OTA used in this cellular toxicological study are reasonable and effectively induce mesangial cell cytotoxicity via a NADPH oxidase-derived ROS-mediated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide production was measured in total cell homogenates by using lucigenin-derived chemiluminescence as described previously [31]. Briefly, 50 μg of protein was diluted in 500 μl of 50 mM phosphate buffer containing 1 mM EGTA and 150 mM sucrose.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, many research studies have been conducted to suggest supplemental agents to confer additional protection for the kidney against CYCinduced toxicity. These supplemental agents may include herbal drugs [3][4][5] , endothelin-1 receptor antagonists 6 , antihypertensive drugs or β-blockers [7][8][9] , NADPH oxidase activity inhibitor 10 , antioxidants 11 , omega-3 fatty acids 12 , apelin peptide 13 , and/or renin inhibitor 14 . Gender and sex hormones are also important factors that influence the effects of CYC [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%